PENGARUH PESAN PERSUASIF TERHADAP TINGKAT KESUKAAN PESAN LINGKUNGAN PADA PROGRAM ONE RIDE ONE SEED ( Analisis Isi Unggahan Instagram @Bluebirdgroup ) - RIFA QURROTU AINIE (2020)
In a big city like Jakarta, the air quality is bad most of the year that is caused by the smoke of motor vehicles. Therefore, the Bluebird Group is determined #BirukanLangitJakarta by conducting a One Ride One Seed Program in an effort to minimize air pollution. The study aims to determine the impact of a persuasive message on the favorite level of environmental messages in the One Ride One Seed program. The theory used in this study was a persuasive theory according to Robert B. Cialdini. This research was conducted using a quantitative approach with the analysis of the analytical content research method. The population and sample of this research is an Instagram post @Bluebirdgroup on One Ride One Seed program with 13 posts. Data processing techniques are processed using coding sheets and SPSS programs (Product statistics and Service Solution) version 26. The results show that posts on the One Ride One Seed program on Instagram @Bluebirdgroup use five of the six persuasive message strategies. The most widely used strategy is the reciprocation strategies with a percentage of 55% and an unused strategy is the strategy authority of 0%. Based on the correlation test calculation, the result of strong relationship between the persuasive message strategy (variable X) to the favorite level (variable Y) and the calculation of coefficient of determination there is a considerable influence between variable X to variable Y. Thus calculation X with Y t count > T table, then it can be deduced Ho rejected and Ha accepted.